Manajemen Kurikulum dan Sistem Penilaian di Sekolah Tinggi Pariwisata Bandung - Wahyudin Wahyudin; Hanafiah Hanafiah; Agus Nana Supena (IAIN Ternate, 2021)
This research aims to find out how the BandungTourism College in theimplementation of the curriculum management systemand assessment has beenrunning according to procedures and even supervised directly from the CentralMinistry of Tourism, this makes STP Bandung a Tourism College which has a big namein the field of tourism in Indonesia. In particular, this study aims to obtain informationand empirical analysis of: 1) learning management at STPBandung. 2) curriculum atSTP Bandung 3) assessment of learning at STPB Bandung